Recurrent abdominal pain in childhood. - Bufler, P; Gross, M; Uhlig, H (2011)
BACKGROUND: Chronic, recurrent abdominal pain is common among children and adolescents. It interferes with everyday life, causes absence from school, and leads to frequent medical consultations, often involving burdensome diagnostic testing and protracted attempts at treatment. METHOD: Selective review of the literature. RESULTS: Organic causes should be ruled out with a thorough medical history and physical examination and a small number of laboratory tests. The pediatric Rome III criteria include valid diagnostic criteria for functional abdominal pain in childhood. The available data imply that this condition is best treated with cognitive behavioral therapy, rather than with medications or dietary measures. CONCLUSION: A systematic approach to chronic recurrent abdominal pain in children and adolescents is key to ruling out organic diseases while avoiding unnecessary tests and treatments.